The Impact of Social Media on Academic Performance of Hindustan College of Arts and Science, Chennai - E Kalaichelvi, E Kalaichelvi; S.Jayakani, S.Jayakani (Journal of Neonatal Surgery, 2025)
The present paper focused on the outcome of social media on academic work performances for Hindustan College of Arts and Science in Chennai. This study is based on primary data collection through a Google form from college students during the 2022–2023 academic years. The study revealed that nowadays both male and female students addicted in social media, and most of the students use Instagram 57% of social media sites. Therefore, the results revealed that the students spent a maximum of 2 to 3 hrs per day in social media groups. Moreover, the results of the study show that most students (98%) do not use social media for educational working or to develop their knowledge